Upaya Peningkatan Overall Equipment Effectiveness Pada Mesin Pellet di PT X - Thymoti David Kembi; Benedictus Rahardjo (Jurnal Titra, 2019)
PT X is an industry that running the fodder production. Each machine in this industry has important role to produce the fodder, so it has to be well maintain for the best performance and result. Overall Equipment Effectiveness (OEE) used to measure the machine effectiveness. Maintenance department has settle the target of OEE that is 60%, but in realization pellet machine 1 and 8 only got 59.6% and 56.32%. An effort to improve OEE is for minimize the biggest losses from six big losses and the biggest Downtime from pellet machine 1 and 8. The biggest losses that causing OEE getting low at pellet machine 1 and 8 is because small stop and slow running losses, while the top downtime from both of the machine is cooler clean-up and waiting for mixer. Main cause from the problem above is obtained by using the fishbone diagram. Each cause is analyzed to obtain the solution. One of the solution is to provide time on pellet machine 1 and 8 for clean-up, checking, and/or repairing by 1.61 hours and 0.9 hours at the same time. The solution resulted in an increase of OEE on pellet machine 1 and 8 by 3.44% and 4.54%.